2022
DOI: 10.3390/colloids6020027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oil Phase on the Inversion of Pickering Emulsions Stabilized by Palmitic Acid Decorated Silica Nanoparticles

Abstract: Pickering emulsions stabilized by the interaction of palmitic acid (PA) and silica nanoparticles (SiNPs) at the water/oil interface have been studied using different alkane oil phases. The interaction of palmitic acid and SiNPs has a strong synergistic character in relation to the emulsion stabilization, leading to an enhanced emulsion stability in relation to that stabilized only by the fatty acid. This results from the formation of fatty acid-nanoparticle complexes driven by hydrogen bond interactions, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 38 publications
1
15
1
Order By: Relevance
“…The increase in the particle concentration is associated with a reduction in the emulsion viscosity, which leads to a worsening of the emulsion stability. This is in agreement with the stabilization of the interface mediated by the steric hindrance associated with the particle adsorption to the fluid interface [17,45]. On the other hand, a very important aspect of the rheological behavior of Pickering emulsions for their practical use is their thickening character.…”
Section: Rheology Of Pickering Emulsionssupporting
confidence: 81%
See 2 more Smart Citations
“…The increase in the particle concentration is associated with a reduction in the emulsion viscosity, which leads to a worsening of the emulsion stability. This is in agreement with the stabilization of the interface mediated by the steric hindrance associated with the particle adsorption to the fluid interface [17,45]. On the other hand, a very important aspect of the rheological behavior of Pickering emulsions for their practical use is their thickening character.…”
Section: Rheology Of Pickering Emulsionssupporting
confidence: 81%
“…However, the development of Pickering emulsions for cosmetic applications is limited due to the scarce number of available studies dealing with the use of cosmetically acceptable compounds. In fact, most of the studies about Pickering emulsions deal with the use of non-biocompatible oil phases, including toluene, n-dodecane or hexadecane, which limits the validity of the extracted conclusions because the oil nature can strongly modify the emulsion stability [17]. This was explored by Wu et al [62] by preparing Pickering emulsions stabilized with silica nanoparticles (diameter of 160 nm) using different cosmetically acceptable oils (silicone oils and ester oils).…”
Section: Pickering Emulsions In Cosmeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pickering emulsions, 41,52 has been successfully demonstrated, it is largely from the formation of fatty acid-silica or calcium carbonate nanoparticle complexes driven by relatively stronger hydrogen bond interactions, promoting hydrophobization, favouring particle attachment at the fluid interface, and minimizing droplet coalescence. This is not the exact case observed in our experiments.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…39 In addition, the hydrophobicity of the long carbon chain of palmitic acid plays an interesting role in the stabilization of Pickering emulsions. 40,41 A few studies have been reported on the stabilization of Pickering emulsions by mixing with palmitic acid. Santini et al showed interfacial properties of palmitic acid against an aqueous dispersion of colloidal silica dependent upon adsorption and complexation leading to the stabilization of the corresponding water-in-hexane emulsions.…”
Section: Introductionmentioning
confidence: 99%